The Students’ Problems in Writing Descriptive Text at Seventh Grade Students of Smp Negeri 3 Samarinda - Suriyanti, Suriyanti; Toba, Rostanti; Komariah, Anis (Borneo Journal of Language and Education, 2022)
Writing skill is one of the abilities that students must be mastered. By writing, students can express ideas, opinions, and feelings. Based on the junior high school curriculum, several basic competencies students must achieve in writing English texts. The competencies to help students develop their skills and produce simple, functional written texts. Descriptive text is a basic competency that is difficult for students to learn. This is because students need help to pour writing ideas into a text. This research aimed to find out the problems of students in writing descriptive texts faced by seventh-grade students of SMP Negeri 3 Samarinda. This research uses descriptive qualitative methods. The researcher only took 2 classes out of a total of 9 classes, namely 7A and 7E, with a total of 69 students as subjects. The researcher used several instruments to collect the data: writing tests, questionnaires, and teacher interviews. The results of this research indicate that students need help writing descriptive texts in content, organization, grammar, vocabulary, and mechanics. However, from the results obtained, students’ most significant problem in writing is a mechanical, organization, and vocabulary. From the results of the writing test, the average score of students was 47%, with scores of contents (141), organization (126), grammar (131), vocabulary (130), and mechanics (122). The questionnaire result showed that students who support this problem experience difficulties in mechanics, organization, and vocabulary, with a total score of 54.8%.